Aliso Canyon Leakage as an Analogue for Worst Case CO2 Leakage and Quantification of Acceptable Storage Loss. (July 2017) - Lindeberg, Erik; Bergmo, Per; Torsæter, Malin; Grimstad, Alv-Arne
Abstract: The Aliso Canyon gas well leakage is used as an analogue to study a possible accident from a CO2 storage site. Because the blowout is the second largest in USA, it can be used as a worst-case blowout analogue for a possible CO2 blowout from an underground CO2 storage. Reservoir modelling and well modelling of the Aliso Canyon case is used to determine the leakage pathway and leakage mechanisms that will mimic the escape history. This data are put in a new model where the gas is replaced by CO2 and a similar accident is simulated. Several factors are different between gas leakage from gas storage and potential leakage from a typical CO2 storage in an aquifer, due to differences in thermodynamic properties and flow properties both along in the leakage pathway and in the porous medium in the storage reservoir. The specific features of the two cases are compared and show that as the risk elements are very different, remediation measures will be different. The escape rate is significant lower for the CO2 scenario than the observed gas escape from Aliso Canyon gas well (4.9 Sm 3 /s respectively 21.3 Sm 3 /s). While 2.8% of the stored gas was lost at the Aliso Canyon leak, the corresponding loss from a CO2 well if the facility was used for CO2 storage would be 0.37%. Due to the high density of CO2, the well pressure at the rupture was less than half than for CO2 compared to gas, which will make remediation easier.